NAGEKEO: ANTARA KENYATAAN DAN HARAPAN MENUJU PERTANIAN YANG BERKELANJUTAN - FATIMA, IMACULATA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Agricultural development in Nagekeo is an expectation of all the people. For this reason the government must work together with the people to design an appropriate plan on agricultural development based on principle: indignity, modernity, and sustainablelity for achieving wealthy people. Some ideas that may be considered like: (1) biophysics aspect (maintenance the soil quality, to improve the land productivity and plant productivity); (2) Irrigation system; (3) Exploitation all the soil-water resource; (4) Management dry land with three strata, agroforestry, and wetland (rice, Azolla, Tiktok, and Fish); (5) To increase networking system; (6) To apply appropriate technology; (7) To develop infrastructure wisely; (8) To manage all the information’s based on the need; (9) To empower the economic of the farmers through cooperation unit.
Keywords: Development, Agriculture, Sustainability, and Nagekeo Flores NTT